PENATALAKSANAAN HIPERTENSI DENGAN RELAKSASI OTOT PROGRESIF PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA BUDI LUHUR KOTA JAMBI - Hasyim Kadri; Salvita Fitrianti (Jurnal Abdimas Kesehatan (JAK), 2019)
The high hypertension in Jambi City where the elderly are individuals who are prone to hypertension. Elderly people in Jambi City can be found in the community, one of them is Budi Luhur Jambi Tresna Werdha Home (PSTW). Social institutions are residential institutions with the elderly who are physically or healthily still independent, but have limitations in the socio-economic field. According to the PSTW Budi Luhur Jambi elderly people can still experience diseases such as hypertension. The number of elderly people suffering from hypertension at Budi Luhur PSTW in Jambi City in November 2018 amounted to 22 elderly with a total of 9 men and 13 women, out of a total of 70 elderly in the Budi Luhur PSTW in Jambi City. Tareget the outcome of this activity officers and sufferers can do progressive muscle relaxation techniques in hypotensive patients at Budi Luhur PSTW, Jambi City